An international standardized dataset and map of the Ahr River catchment geology, Germany - Svenja Scholz; Henriette Westermann; Ronja Hegemann; Mara Popp; Tobias Richter; Markus Lothar Fischer; Christoph Zielhofer (PANGAEA, 2023)
This dataset provides a detailed geological map of the entire Ahr River catchment, which is located in Western Germany. The geological information was acquired using a transfer of the German geological terms into the international stratigraphic notation. Information about the geology was provided by publicly sourced data released by the German federal states North Rhine-Westphalia and Rhineland-Palatinate. The dataset includes information about the international stratigraphy, the corresponding German unit, and the lithology in English and German. The dataset is essentially useful for catchment-scale research regarding the causes and consequences of the July 2021 flooding of the Ahr River.